Tourism sustainability on Santa Cruz (Galapagos): a multidimensional analysis based on UN-Tourism indicators - Guerrero Basurto, Jhon Kevin (2026)
Introduction and objective: This study sought to analyze in a multidimensional way the tourism sustainability of Santa Cruz Island, in the Galapagos archipelago, considering the importance of the balance between tourism development and the conservation of the natural and cultural heritage of the destination. Methodology: A non-experimental, exploratory and descriptive research was developed, based on the deductive method. To collect information, a structured survey was applied to three interest groups: local residents, national tourists and foreign tourists. The questionnaire was designed with a Likert scale based on tourism sustainability indicators from UN-Tourism, and the traffic light technique was used as an evaluation tool. The dimensions analyzed were environmental, economic and sociocultural. Results: The results show an uneven performance between the dimensions studied. Strengths were identified in the economic sphere and in sociocultural coexistence; however, weaknesses were also detected in the environmental dimension, especially related to waste management, tourist transport and the limited visibility of environmental certifications. Conclusions: The findings reflect the need to design proposals aimed at strengthening tourism sustainability on Santa Cruz Island, in order to improve the balance between tourism growth and the conservation of its natural and cultural resources.